Tree regeneration spatial patterns in ponderosa pine forests following stand-replacing fire: influence of topography and neighbors - Ziegler, Justin P., author; Hoffman, Chad M., author; Fornwalt, Paula J., author; Sieg, Carolyn H., author; Battaglia, Mike A., author; Chambers, Marin E., author; Iniguez, Jose M., author; MDPI, publisher (Colorado State University. Libraries, 2017)
Shifting fire regimes alter forest structure assembly in ponderosa pine forests and may produce structural heterogeneity following stand-replacing fire due, in part, to fine-scale variability in growing environments. We mapped tree regeneration in eighteen plots 11 to 15 years after stand-replacing fire in Colorado and South Dakota, USA. We used point pattern analyses to examine the spatial pattern of tree locations and heights as well as the influence of tree interactions and topography on tree patterns. In these sparse, early-seral forests, we found that all species were spatially aggregated, partly attributable to the influence of (1) aspect and slope on conifers; (2) topographic position on quaking aspen; and (3) interspecific attraction between ponderosa pine and other species. Specifically, tree interactions were related to finer-scale patterns whereas topographic effects influenced coarse-scale patterns. Spatial structures of heights revealed conspecific size hierarchies with taller trees in denser neighborhoods. Topography and heterospecific tree interactions had nominal effect on tree height spatial structure. Our results demonstrate how stand-replacing fires create heterogeneous forest structures and suggest that scale-dependent, and often facilitatory, rather than competitive, processes act on regenerating trees. These early-seral processes will establish potential pathways of stand development, affecting future forest dynamics and management options.
Keywords: pair-correlation function; mark-correlation function; high-severity fire; species interaction; topographic niche; vegetation assembly; early-seral forests; secondary succession